STEREOTYPING IN THE CLASSROOM: PROMOTING INTERCULTURAL COMMUNICATIVE COMPETENCE IN ENGLISH LANGUAGE TEACHING - Aufa, Fauzul (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2013)
Teaching and learning languages involve more than targeting grammatical and lexical knowledge. To achieve communicative competence in English as a Foreign Language (EFL) context, EFL learners need to develop their intercultural competence. This article proposes one of influential aspects of target culture (i.e. stereotypes) that may be encountered by EFL learners in learning. Further, the author argues why learners need to be exposed with stereotyping features across cultures and how this can be incorporated into English Language Teaching (ELT) by providing an example of teaching activities that can be adapted in a language classroom. Briefly, it is expected that this article may provide EFL teachers with a better understanding of integrating intercultural elements of a target language in their teaching practice. In turn, this may be useful to facilitate EFL learners in developing their intercultural communicative competence particularly with regards to cultural stereotype features.